Purification and characterization of copper zinc superoxide dismutase of the patients reperfused after myocardial infarction - PUSHPA B. NEGI; VINEET AWASTHI; GURJEET KAUR (International Journal of Pharma and Bio Sciences, 2018)
Amongst the popular lifestyle diseases, cardiovascular disorders have established a relation with the increased ROS production. Reperfusion after Myocardial infarction (MI) through being explored by various researchers still provides room for the study related to the behaviour of Cu-Zn Superoxide dismutase (SOD). The enzyme under investigation was purified by using various biochemical techniques from the erythrocytes of patients reperfused after MI. Further spectrophotometric estimations were conducted with regard to different additives. The Cu-Zn SOD was purified to homogeneity from the erythrocytes of patients and healthy individuals. In the present study purification attained was 631 fold, specific activity 896 units per mg protein and 3% recovery of activity from patients. The molecular weight of the purified enzyme determined by gel filtration and sodium dodecyl sulphate- polyacrylamide gel electrophoresis (SDS-PAGE) was found to be 37 kDa and 18.6 kDa respectively. The enzyme purified from both the patients and healthy individuals showed identical UV-Visible absorption spectra and molecular weight. Patient group showed alterations in the catalytic behaviour of the enzyme under study when compared to the healthy controls treated with metal ions (Cu2+, Zn2+, Ca2+, Mg2+, Hg2+), thiols (β-mercaptoethanol, dithiothreitol, cysteine, reduced glutathione), reducing agents (L-ascorbic acid), oxidizing agents ( hydrogen peroxide) and -SH binding agents (para-chloromercuric benzoate, iodoacetamide, N-ethylmaleimide). The higher propensity for inhibition in the presence of cystine, sodium azide (NaN3), sulphanilamide, diethyl di-thiocarbamate (DDC) and sodium dodecyl sulphate (SDS) was observed whereas ethylene di-amine tetra acetic acid (EDTA) activated enzyme by 303 % and 144 % in patients and controls respectively.